Detecting the surface salinity signature of Gulf Stream cold‐core rings in Aquarius synergistic products. Issue 2 (12th February 2015) - Umbert, M.; Guimbard, S.; Lagerloef, G.; Thompson, L.; Portabella, M.; Ballabrera‐Poy, J.; Turiel, A.
Abstract: New sea surface salinity (SSS) observations derived from satellite remote sensing platforms provide a comprehensive view of salt exchanges across boundary currents such as the Gulf Stream. The high resolution (45 km spatial resolution and 3 day repeat subcycle) of the Soil Moisture and Ocean Salinity (SMOS) observations allows detection (and tracking) of meander and ring structures of the Gulf Stream from SSS maps. These structures are, however, not resolved by the relatively lower resolution (100 km and 7 day repeat subcycle) of Aquarius observations. A recently developed fusion technique, based on singularity analysis, is applied in this study to reconstruct these mesoscale (from 100 km and 3 days) features in Aquarius‐derived products. New quarter‐degree SSS maps are obtained by fusing Aquarius data with three different geophysical templates: sea surface height (SSH) from AVISO, SSS from SMOS, and sea surface temperature (SST) from AVHRR. The proposed method exploits the theoretical correspondence among the singularity exponents of different maps of ocean‐surface remotely sensed scalar fields. The analysis results over the year 2012 show that merging Aquarius with SSH data provides a series of negative salinity anomalies that better collocate with the position of the cyclonic eddies identified from sea level anomaly maps. This result is consistent with the hypothesis that this SLA derived cyclonic eddies in this area are indeed CCRs shed off the GS. Key Points: Low spatiotemporal resolution Aquarius L3 maps poorly resolve CCRs A data fusion technique is used to fuse Aquarius with other satellite products Aquarius L4 product fused with SSH best resolves CCR SSS signature and evolution